Pengaruh Work-Life Balance dan Lingkungan Kerja terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kota Bekasi - Annisa, Euis; Hastasari, Ratih (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the influence of work-life balance and work environment on employee performance at the Bekasi City Population and Civil Registration Office. The type of data used in this study is quantitative research data and the data is processed using SPSS version 27. The sampling technique that will be used is a saturated sample with a census of 99 people. The data sources used in this study are primary data such as observation and questionnaire distribution. Meanwhile, secondary data used in this study is literature study. The results of this study used several testing methods, namely, Data Quality Test, Classical Assumption Test, Hypothesis Test, and Determination Coefficient Test. Based on the test results of this study indicate that there is a positive and significant influence between work-life balance and employee performance as indicated by the results of the t-test of 6.380> 1.984 with a significance value of 0.000 1.984 and a significance of 0.030> 0.05. Based on the F test, work-life balance and work environment together have a significant influence on employee performance at the Bekasi City Population and Civil Registration Office with a value of 44.280 > 3.09 and a sig value of 0.000 < 0.05.